Temporal interaction of information and belief - Giacomo Bonanno (University of California, Department of Economics, 2005)
The temporal updating of an agent's beliefs in response to a flow of information is modeled in a simple modal logic that, for every date t , contains a normal belief operator B_t and a non-normal information operator I_t which is analogous to the 'only knowing' operator discussed in the computer science literature. Soundness and completeness of the logic are proved and the relationship between the proposed logic and the AGM theory of belief revision is discussed.
Keywords: 330